Cointegration analysis of sesame prices in Ethiopian commodity exchange warehouses - Tazeze, Aemro; Kassie, Girma T.; Abate, Gashaw T.; Worku, Yonas; Asnake, Woinishet; Minot, Nicholas (International Food Policy Research Institute, 2024)
This study examines the cointegration of sesame market prices in eight Ethiopian Commodity Exchange (ECX) warehouses and its implications for improving the functioning of sesame markets. We analyzed 489 weekly market price data points for each of the eight ECX warehouses, covering the period from end of 2014 to mid-2024. We estimate the Multivariate Vector Error Correction Model (ECM) to analyze short- and long-term spatial price adjustments across warehouses. Of the eight warehouses, six showed significant spatial integration. The VECM results showed effective price transmission and strong short- and longterm market relationships. Short-term dynamics particularly revealed complex interactions. These findings highlight the varying impacts of price fluctuations between warehouses and the need to understand these interactions for better strategic decision making, resource allocation, and pricing strategy refinement. Furthermore, accelerating the speed of price pass through is vital to improve the livelihoods of sesame farmers in Ethiopia.